DDC-Promoter-Driven Chemogenetic Activation of SNpc Dopaminergic Neurons Alleviates Parkinsonian Motor Symptoms - Seo, Dong-Chan; Ju, Yeon Ha; Seo, Jin-Ju; Oh, Soo-Jin; Lee, C. Justin; Lee, Seung Eun; Nam, Min-Ho (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Parkinson's disease (PD) is a neurodegenerative disorder with typical motor symptoms. Recent studies have suggested that excessive GABA from reactive astrocytes tonically inhibits dopaminergic neurons and reduces the expression of tyrosine hydroxylase (TH), the key dopamine-synthesizing enzyme, in the substantia nigra pars compacta (SNpc). However, the expression of DOPA decarboxylase (DDC), another dopamine-synthesizing enzyme, is relatively spared, raising a possibility that the live but non-functional TH-negative/DDC-positive neurons could be the therapeutic target for rescuing PD motor symptoms. However, due to the absence of a validated DDC-specific promoter, manipulating DDC-positive neuronal activity has not been tested as a therapeutic strategy for PD. Here, we developed an AAV vector expressing mCherry under rat DDC promoter (AAV-rDDC-mCherry) and validated the specificity in the rat SNpc. Modifying this vector, we expressed hM3Dq (Gq-DREADD) under DDC promoter in the SNpc and ex vivo electrophysiologically validated the functionality. In the A53T-mutated alpha-synuclein overexpression model of PD, the chemogenetic activation of DDC-positive neurons in the SNpc significantly alleviated the parkinsonian motor symptoms and rescued the nigrostriatal TH expression. Altogether, our DDC-promoter will allow dopaminergic neuron-specific gene delivery in rodents. Furthermore, we propose that the activation of dormant dopaminergic neurons could be a potential therapeutic strategy for PD.